2013
DOI: 10.1186/1746-6148-9-206
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, pathological and histological findings in four Danish pig herds affected by a new neonatal diarrhoea syndrome

Abstract: BackgroundNeonatal diarrhoea is a frequent clinical condition in commercial swine herds, previously regarded to be uncomplicated to treat. However, since 2008 it seems that a new neonatal diarrhoeic syndrome unresponsive to antibiotics and common management practices has emerged. Routine laboratory examinations have not detected any pathogen related to this syndrome. The primary purpose of this study was to evaluate if well-known enteric pathogens could be associated with outbreaks of neonatal diarrhoea, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 13 publications
7
54
2
1
Order By: Relevance
“…The existence of an NNPDS unassociated with previously acknowledged enteropathogens has therefore been suggested (Kongsted et al, 2013). Our investigation of NPD in 10 Swedish herds indicated that bacteria commonly associated with piglet diarrhoea were rare (ETEC), absent (Clostridium perfringens type C) or apparently unrelated to the diarrhoea (Clostridium perfringens type A and Clostridium difficile).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The existence of an NNPDS unassociated with previously acknowledged enteropathogens has therefore been suggested (Kongsted et al, 2013). Our investigation of NPD in 10 Swedish herds indicated that bacteria commonly associated with piglet diarrhoea were rare (ETEC), absent (Clostridium perfringens type C) or apparently unrelated to the diarrhoea (Clostridium perfringens type A and Clostridium difficile).…”
Section: Discussionmentioning
confidence: 91%
“…Flaccidity and dilation of the intestine were common among the diarrhoeic piglets, a gross pathology consistent with NNPDS (Kongsted et al, 2013). However, these findings, as well as the hyperaemia of the small intestine in some piglets, are common in neonatal diarrhoea irrespective of its cause (Brown et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since 2008, field experiences of a new diarrhoeic syndrome have been reported in several countries including Sweden, referred to by some authors as the New Neonatal Porcine Diarrhoea Syndrome (NNPDS) (Kongsted et al, 2013;Melin et al, 2010). No known pathogens or management factors causing the outbreaks has to our knowledge yet been identified.…”
Section: Enteritismentioning
confidence: 96%
“…In recent years however, reports from a number of countries, including Sweden, describe problems with NPD despite the use of previously effective preventive measures [1720]. The underlying causes for this problem, by some referred to as new neonatal porcine diarrhoea syndrome (NNPDS), is currently unknown and hitherto well-known porcine enteropathogens seem to be of minor importance [17, 19, 20]. …”
Section: Introductionmentioning
confidence: 99%